A Case: The Strategy of Corneal Ulcers: Poster Presentation - Case Report - General practitioner - Oktaliani, Rahayu; Waslan, Kuswaya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal ulcers are considered an ophthalmologic emergency because of their potential to permanently impair vision or perforate the eye. Accurate and quick diagnosis and prompt treatmentis a key to improve clinical and visual outcomes in cases of corneal ulceration. Case Illustration : In this paper, we present the case of male 40-year-old presented with complaints of pain and defective vision in the right eye. Visual examination of the right eye is 1/~. It was found, palpebral edema, hyperemic tarsal conjunctiva. The bulbar conjunctiva showed conjunctival injection, ciliary injection. The cornea looks completely cloudy, the surface is not slippery, infiltrates and edema. The patient was treated with medical and surgical therapy, and then the patient’s have a good clinical response and was able to return to work. Discussion : The diagnosis of corneal ulcers was established based on history, physical examination and clinical examination using a slit lamp and laboratory examinations. Patient's examination revealed the presence of Candida albicans. This examination is important to distinguish the cause of the corneal ulcer so that it can help select an adequate therapy. Conclusion : Indonesian farmers have highrisk of fungal corneal ulcers. Fungal corneal ulcers is important cause of corneal blindness all over the world especially in develoving countries. Fungal corneal ulcers can diagnosis by slitlamp biomicroscopic examination and culture are essential for early specific diagnosis and must be taken consideratiaon to establish the most effective treatment and avoid severe complications